EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VII SMP - Ayu Lestari; Nur Kholisah Latuconsina; Andi Ulmi Asnita (Al Asma: Journal of Islamic Education, 2019)
This research investigates the effectiveness of Think Pair Share (TPS) cooperative learning model in enhancing seventh grade student’s mathematical communication at SMP Negeri 2 Patalassang in Gowa Regency. It employs quasi experimental research design with non-equivalent control group design to investigate the issue. The population of this research is divided into 4 classes and decided with simple random sampling technique. The instruments used in this research consist of pre-test and post-test of mathematical communication ability. The data were analysed using descriptive and inferential statistic. The research findings suggest that the results of the descriptive analysis show a high level of student’s mathematical communication ability when taught with the TPS model, indicated by an average score of 78.2926 with a percentage of 66.667%. However, the findings also signify an equally high level of student’s mathematical communication ability without being taught with TPS model, indicated by an average score of 74.1944 with a percentage of 88.111%. The results of the inferential analysis, meanwhile, show that there is a significant difference of student’s mathematical communication ability between the classes who were taught with the TPS model and those who were not, signified. Furthermore, an advanced testing shows that the TPS learning model is more effective in enhancing student’s mathematical communication ability than the learning without the implementation of the TPS model. AbstrakPenelitian ini bertujuan untuk mengetahui apakah model pembelajaran Kooperatif tipe Think Pair Share (TPS) efektif dalam meningkatkan kemampuan komunikasi matematis peserta didik kelas VII SMPN 2 Patalassang Kabupaten Gowa. Penelitian ini merupakan penelitian eksperimen dengan jenis penelitian quasi experimental design dengan non-equivalent control group design. Populasi dalam penelitian ini terbagi ke dalam 4 kelas kemudian dengan penentuan sampel menggunakan simple random sampling. Instrumen yang digunakan berupa tes kemampuan komunikasi matematis terbagi atas pretest dan posttest. Teknik analisis yang digunakan adalah statistik deskriptif dan statistik inferensial. Hasil analisis deskriptif menunjukkan bahwa rata-rata kemampuan komunikasi matematis siswa dengan model pembelajaran kooperatif tipe TPS adalah 78,2926 berada pada kategori tinggi dengan persentase 66,667% dan rata-rata kemampuan komunikasi matematis siswa tanpa model pembelajaran kooperatif tipe TPS adalah 74,1944 pada kategori tinggi dengan persentase 88,111%. Hasil analisis inferensial menunjukkan bahwa terdapat perbedaan yang signifikan antara kemampuan komunikasi matematis siswa antara kelas yang diajar dengan model pembelajaran kooperatif  tipe TPS dengan kelas tanpa model pembelajaran kooperatif tipe TPS. Selanjutnya, hasil uji lanjut menunjukkan bahwa pembelajaran dengan model pembelajaran kooperatif tipe TPS lebih efektif meningkatkan kemampuan komunikasi matematis siswa dibandingkan dengan tanpa model pembelajaran kooperatif tipe TPS.